Photosystem I-based Biophotovoltaics on Nanostructured Hematite - Ocakoglu, Kasim; Krupnik, Tomasz; van den Bosch, Bart; Harputlu, Ersan; Gullo, Maria Pia; Olmos, Julian David Janna; Kargul, Joanna (Wiley-V C H Verlag Gmbh, 2014)
The electronic coupling between a robust red algal photosystem I (PSI) associated with its light harvesting antenna (LHCI) and nanocrystalline n-type semiconductors, TiO2 and hematite (alpha-Fe2O3) is utilized for fabrication of the biohybrid dye-sensitized solar cells (DSSC). PSI-LHCI is immobilized as a structured multilayer over both semiconductors organized as highly ordered nanocrystalline arrays, as evidenced by FE-SEM and XRD spectroscopy. Of all the biohybrid DSSCs examined, alpha-Fe2O3/PSI-LHCI biophotoanode operates at a highest quantum efficiency and generates the largest open circuit photo-current compared to the tandem system based on TiO2/PSI-LHCI material. This is accomplished by immobilization of the PSI-LHCI complex with its reducing side towards the hematite surface and nanostructuring of the PSI-LHCI multilayer in which the subsequent layers of this complex are organized in the head-to-tail orientation. The biohybrid PSI-LHCI-DSSC is capable of sustained photoelectrochemical H-2 production upon illumination with visible light above 590 nm. Although the solar conversion efficiency of the PSI-LHCI/hematite DSSC is currently below a practical use, the system provides a blueprint for a genuinely green solar cell that can be used for molecular hydrogen production at a rate of 744 mu moles H-2 mg Chl(-1) h(-1), placing it amongst the best performing biohybrid solar-to-fuel nanodevices.
Keywords: Sensitized Solar-Cells; Cyanidioschyzon-Merolae; Enhanced Photocurrent; Angstrom Resolution; Electron-Transfer; Molecular Wire; Supercomplex; Performance; Complexes; Backbone